Contemporary Industrial Relations Ideologies: A Study of Canadian Academics - Godard, John (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1992)
This study begins by identifying five competing ideologies characteristic of industrial relations in the postwar era. It then draws upon a survey data to explore the content, structure, and covariates of the industrial relations ideologies of Canadian academies. The findings are threefold. First, it would appear that there is substantial support for reforms to the Canadian System which strengthen the rights of workers and their unions. Yet there is also support for more cooperative labour-management relations in the workplace. This suggests an ideological shift to both the left andthe 'right' of orthodox pluralism, embodied in a 'neo-institutionalist' ideology. Second, factor analysis of 65 items strongly suggests that ideology varies along a single dimension, from 'right' to 'left'. Third, scholars specializing in IR or affiliated with an IR school tend to be slightly more 'leftwing' than their counterparts in economies and management. The implications of these findings for the field are briefly discussed.